Should I stay or should I go? The effect of London's terrorist attack on the educational choices of Muslims - Diego Astorga-Rojas (SERIEs - Journal of the Spanish Economic Association, 2023)
This paper evaluates how the July 2005 London terrorist attacks affected Muslim teenagers' education plans and decisions. The attacks triggered a violent backslash against the Muslim community, which could have affected their incentives to continue in full-time education. I examine panel data on educational attitudes from the "Next Steps" Survey in England and use the month the survey was administered to divide individuals into treatment and control groups. I find that the attacks negatively affected the education plans of Muslims, but not those of any other major religious group. The probability of planning to continue in non-compulsory full-time education decreased by around 4.4% points for Muslims after the attacks. This corresponds to a 69% increase in individuals who were not sure whether to continue or drop out of full-time education. However, this change in plans appears to be a temporary reaction, since it did not affect students' actual decisions two years later.
Keywords: I20; I29; J15; 330; Education; Terrorism